A Fluorophore‐Free Chemodosimeter for H2S with Luminescence Turn–on Response: Hyrdogen Sulphide Sensing in Garlic Extract. Issue 15 (30th September 2016) - Maiti, Kalipada; Mahapatra, Ajit Kumar; Maji, Rajkishor; Mondal, Sanchita; Ali, Syed Samim; Gangopadhyay, Ankita; Manna, Saikat Kumar; Mandal, Sukhendu
Abstract: A novel non‐fluorophoric chemodosimeter, 2‐[4‐Diethylamino‐2‐(4‐nitro‐benzyloxy)‐benzylidene]‐malonic acid diethyl ester (1 ) was developed for the estimation of hydrogen sulphide by exploitation of the ubiquitous reduction of nitro functionality to amino under mild conditions which culminated in the generation of the popular fluorescent moiety, coumarin via tandem nucleophilic addition‐elimination reaction made facile by the structure of the probe molecule. The coumarin moiety produced a brilliant blue fluorescence turn‐on response. Apart from its sensitivity, selectivity and successful application in cellular imaging, a remarkable feature of1 is its capacity to detect H2 S in garlic extract both in presence as well as absence of glutathione which is a crucial player in the pathway for the production of H2 S from garlic extract. Abstract : The first ever report of a novel non‐fluorophoric probe molecule capable of detecting and estimating hydrogen sulphide via reduction of nitro to amino functionality which triggers the formation of a well known fluorogenic species‐ coumarin. Successful application of this probe for detection of H2 S occurring in fresh garlic extract has been possible.